International Olympic Committee consensus-driven guidelines for athlete mental health support at sporting events - Mountjoy, M.; Sloan, S.; Ali-Zada, M.; Bindra, A.; Blauwet, C.; Budgett, R.; Burrows, K.; Currie, A.; Engebretsen, L.; Erdener, U.; Massey, A.; McDuff, D.; et al. (British Journal of Sports Medicine, 2025)
Event-related mental health problems among elite athletes are prevalent. However, empirical details on the development and implementation of a comprehensive mental health support programme at international sporting events are lacking. Therefore, this paper aims to provide consensus-driven, evidence-based recommendations to guide such a development and implementation. An 8-stage process based on the RAND-UCLA Appropriateness Method was adopted to collate and synthesise the available literature on this topic, to identify gaps in the scientific evidence and to enlist expert experience from a multidisciplinary expert panel to fill these gaps. Within such a process, the existing scientific literature was explored while experts (including athletes) were consulted to reach consensus on the recommendations. Accordingly, a robust pre-event plan is required to ensure the successful implementation of a comprehensive mental health programme during sport events, focussing on promotion, prevention, treatment and recovery. During sporting events, according to the defined pre-event plan, various activities targeting athletes, coaches, the entourage, officials or fans should be implemented: for example, educational programmes to decrease stigma, raise awareness and support help-seeking, a mental fitness area for decompression and relaxation, inperson mental health services provided by qualified mental health professionals with sport-specific as well as trauma-informed and violence-informed skills and mental health surveillance in parallel with the existing injury and illness surveillance programmes. Post event, a thorough evaluation of the implemented activities should be conducted while surveillance data should be analysed to identify areas requiring future targeted intervention(s). Also, particular attention should be given to postevent mental health support including the use of decompression interventions to support adjustment, emotional processing and reintegration.